Real-time ultrasound enhances umbilical venous catheters placement in preterm newborns - Cossovel, Francesca; Galdo, Francesca; Ronfani, Luca; Travan, Laura; Bibalo, Cristina; Trappan, Antonella (Frontiers in Pediatrics, 2025)
Objectivesthe study aims to determine whether real-time ultrasound-guided umbilical venous catheter (UVC) insertion could enhance the accuracy of the procedure and reduce the number of x-ray, thereby minimizing radiation exposure of the newborn.MethodsA pre-post study was conducted, comparing outcomes before and after the introduction of ultrasound during catheter placement. All included newborns required placement of the UVC. In the study population (interventional group) the catheter tip was visualized using both ultrasound and radiography, whereas in the in historical cohort (control group) the catheter tip was visualized solely through radiography. Exclusion criteria included hemodynamic instability, known vascular malformations and major congenital malformations.ResultsDuring the study period, 33 eligible neonates underwent tip navigation and were enrolled, all of whom had a centrally-placed UVC. Additionally, 36 newborns were retrospectively identified as control group. The median gestational ages were 34 weeks and 33 weeks respectively for the interventional and control group (p 0.74). The median birth weights were 2,087 (1,400–3,220) g and 1,966 (1,489–2,695) g respectively for the interventional and control group (p 0.67). The catheter was correctly positioned at first attempt in 29/33 (87%) patients with US guidance and 17/36 (47%) in the control group (p < 0.001). The mean numbers of x-rays taken were 1.1 and 1.8 respectively for the interventional and control group (p < 0.001). In the control group, the mean number of antero-posterior thoracoabdominal radiograph (TAR) ranged from 1 to 3 for each patient.ConclusionIn conclusion, ultrasound could be the standard of care for umbilical catheter placement, ensuring accurate vessel assessment and real-time visualization. Despite our limited sample, our findings highlight its superior precision and safety, reducing complications and the need for radiography. Integrating ultrasound into daily neonatal practice can improve catheter placement and patient outcomes.